Impacts of Technological Development and High Tech Product Exports on Economic Complexity Index: The Case of Turkey - Şeker, Ayberk (Manisa Celal Bayar University, 2019)
Determining sectors invested in is greatly important for countries to gain competitive advantages in international trade.. In this direction, it is beneficial for countries to reveal the effects of the level of technological development on exports. The economic complexity index measures the density of information and the productive output of an economy by considering the knowledge intensity of products that a country exports. The economic complexity index, which shows the intensity of information in exports, reveals both the technological density and the product diversity of countries' exports. In the scope of study, the relationships between high technology exports, technological developments, capital formation and the economic complexity index that reveal the competitive advantage in international trade for Turkey has been analyzed. As a result of Johansen and Gregory-Hansen cointegration tests, long-term relationships between economic complexity index, high-tech product exports, domestic patent applications and fixed capital investments have been determined. Then, long-term coefficients and causality relationships among the variables have been estimated. As a result of causality analysis, bidirectional causality relationship between economic complexity index, high-tech product exports and resident patent applications is seen. On the other hand, unidirectional causality relationships from gross fixed capital investments to economic complexity index, high-tech product exports and resident patent applications are determined.Key Words: Economic Complexity Index, High-Technology Export, Technological Development, Gregory-Hansen Cointegration, Granger Causality.             JEL Classification: F10, O11, O14, O30.

Ülkelerin uluslararası ticarette rekabet üstünlüğünü elde edebilmeleri için teknoloji yatırımları gerçekleştirmeleri ve yüksek teknolojili ürün ihracatına yönelmeleri büyük önem arz etmektedir. Bu doğrultuda, teknolojik gelişme düzeyinin ihracat üzerindeki etkilerinin ortaya koyulması gerekmektedir. Ekonomik karmaşıklık endeksi, bir ülkenin ihraç ettiği ürünlerin bilgi yoğunluğunu göz önüne alarak bir ekonominin bilgi yoğunluğunu ve üretken çıktısını ölçmektedir. İhracattaki bilgi yoğunluğunu gösteren ekonomik karmaşıklık endeksi, hem ülkelerin ihracatlarındaki teknoloji yoğunluğunu hem de ürün çeşitliliğini ortaya koymaktadır. Çalışma kapsamında ülkelerin uluslararası ticarette rekabet üstünlüğünü ortaya koyan ekonomik karmaşıklık endeksinin teknolojik gelişme, yüksek teknolojili ürün ihracatı ve sermaye yatırımları ile ilişkisi Türkiye için analiz edilmiştir. Johansen ve Gregory-Hansen eşbütünleşme testleri sonucunda, ekonomik karmaşıklık endeksi ile yüksek teknolojili ürün ihracatı, yerli patent başvuruları ve sabit sermaye yatırımları arasında uzun dönemli bir ilişkinin bulunduğu tespit edilmiştir. Daha sonra ise uzun dönemli katsayı tahmini yapılarak ve nedensellik testleri gerçekleştirilerek değişkenler arasındaki ilişki ortaya koyulmuştur. Nedensellik analizleri sonucunda, ekonomik karmaşıklık endeksi, yüksek teknolojili ürün ihracatı ve yerli patent başvuruları arasında çift yönlü bir nedensellik ilişkisi olduğu görülmüştür. Bununla birlikte, brüt sabit sermaye yatırımlarından ekonomik karmaşıklık endeksi, yüksek teknolojili ürün ihracatı ve yerli patent başvurularına doğru tek yönlü bir nedensellik ilişkisi bulunduğu ortaya koyulmuştur. Anahtar Kelimeler: Ekonomik Karmaşıklık Endeksi, Yüksek Teknolojili Ürün İhracatı, Teknolojik Gelişme, Gregory-Hansen Eşbütünleşme, Granger Nedensellik. JEL Sınıflandırması: F10, O11, O14, O30.
Teknolojik Gelişme ve Yüksek Teknoloji İhracatının Ekonomik Karmaşıklık Endeksi Üzerindeki Etkisi: Türkiye Örneği